2018
DOI: 10.1016/j.jaci.2017.10.051
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood transplantation without in vivo T-cell depletion for children with MHC class II deficiency

Abstract: Fourth, the pattern of IL-12p70, IL-10, and TNF-a production by sorted CD16 11 DC4s incubated for 24 hours with LPS (or R848, data not shown) in the presence or absence of IFN-g was found to be qualitatively and quantitatively almost identical to that displayed by nonclassical monocytes/Mono2s and CD14 dim/2 CD16 11 slan 1 monocytes, but completely different from those by classical monocytes/Mono1s or cDC2s (Fig 2, C). Similarly, CD16 11 DC4s, but not cDC2s or Mono1s, behaved exactly as Mono2s and CD14 dim/2 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Thirty-four patients have been reported previously. 15,21,22 Among the 155 grafts, 38 were in patients with SCID, and 117 were in patients with non-SCID PIDs. Table I shows a full list of patients' diagnoses.…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…Thirty-four patients have been reported previously. 15,21,22 Among the 155 grafts, 38 were in patients with SCID, and 117 were in patients with non-SCID PIDs. Table I shows a full list of patients' diagnoses.…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…Elfeky et al have reported on the use of unrelated cord blood transplantation without serotherapy in 6 patients with MHC class II deficiency, 5 of whom had chronic norovirus infection (48). Other active infections at the time of transplant included: CMV viremia, Pneumocystis jiroveci pneumonia, Echovirus meningitis, and RSV pneumonitis.…”
Section: Hematopoietic Stem Cell Transplantation For Individual Primamentioning
confidence: 99%
“…One hundred forty-seven patients have been previously reported. [25][26][27][28][29] Transplants (441/474) were evaluable for the study. For the excluded patients (33/474), the median day to mortality was 15 days.…”
Section: Patient Characteristicsmentioning
confidence: 99%